Simultaneous Removal of Multicomponent VOCs in Biofilters. Issue 7 (July 2018) - Yang, Chunping; Qian, Hui; Li, Xiang; Cheng, Yan; He, Huijun; Zeng, Guangming; Xi, Jinying
Abstract : Volatile organic compounds (VOCs) are significant atmospheric pollutants that cause environmental and health risks. Waste gases polluted with multiple VOCs often need to be purified simultaneously in biofilters, which may lead to antagonistic, neutral, or synergistic effects on removal performance. Antagonism limits the application of biofilters to simultaneous treatment of multiple VOCs, while synergism has not yet been fully exploited. We review the interactions among multiple target pollutants and the changes in the bioavailability and biodegradability of substrates that are responsible for substrate interactions. Potential strategies for enhancing biofilter performance are then discussed. Finally, we propose further efforts to alleviate antagonism by enhancing bioavailability and biodegradability, and discuss possible challenges to take advantage of synergism. Highlights: The structure of microbial populations plays an important role in the interactions between hydrophobic and hydrophilic VOCs, and the application of specific single species or mixed microorganisms may alter substrate interactions and consequently enhance removal performance. Enhancing the bioavailability of reluctant VOCs can better offset the negative interactions exerted by the cosubstrates. Strategies to alleviate the negative interactions among multiple VOCs will make it possible to employ biofilters for full-scale removal of multiple VOCs. Biofilter performance for hydrophobic VOCs can be enhanced by exploiting the synergistic interactions of hydrophilic substrates. Regulating operational parameters, such as changing the feeding loading rate for every component and alternating the use of some hydrophilic compounds, may be promising strategies.